Presentación No.35 2014 - Editora, La (Facultad de Ciencias Jurídicas de la Universidad Nacional Autónoma de Honduras, 2015)
DOI: http://dx.doi.org/10.5377/lrd.v35i0.1780Revista de Derecho, Vol. 34, Nº 1, Año 2013